The Selective Glucocorticoid Receptor Modulator Cort 113176 Reduces Neurodegeneration and Neuroinflammation in Wobbler Mice Spinal Cord. (1st August 2018) - Meyer, Maria; Lara, Agustina; Hunt, Hazel; Belanoff, Joseph; de Kloet, E. Ronald; Gonzalez Deniselle, Maria Claudia; De Nicola, Alejandro F.
Highlights: Wobbler mice show motoneuron degeneration and glial reactivity in spinal cord. Wobbler mice show evidence of hyperadrenocorticism. CORT113176 is a selective glucocorticoid receptor antagonist. CORT113176 reduced neuroinflammation and motoneuron vacuolation of Wobbler mice. GR antagonists may be a promising therapy for neurodegeneration. Abstract: Wobbler mice are experimental models for amyotrophic lateral sclerosis. As such they show motoneuron degeneration, motor deficits, and astrogliosis and microgliosis of the spinal cord. Additionally, Wobbler mice show increased plasma, spinal cord and brain corticosterone levels and focal adrenocortical hyperplasia, suggesting a pathogenic role for glucocorticoids in this disorder. Considering this endocrine background, we examined whether the glucocorticoid receptor (GR) modulator CORT 113176 prevents spinal cord neuropathology of Wobblers. CORT 113176 shows high affinity for the GR, with low or null affinity for other steroid receptors. We employed five-month-old genotyped Wobbler mice that received s.c. vehicle or 30 mg/kg/day for 4 days of CORT 113176 dissolved in sesame oil. The mice were used on the 4th day, 2 h after the last dose of CORT 113176. Vehicle-treated Wobbler mice presented vacuolated motoneurons, increased glial fibrillary acidic protein (GFAP)+ astrocytes and decreased glutamine synthase (GS)+ cells. There was strong neuroinflammation, shown by increased staining for IBA1+ microglia and CD11b mRNA, enhanced expression of tumor necrosis factor-α, its cognate receptor TNFR1, toll-like receptor 4, the inducible nitric oxide synthase, NFkB and the high-mobility group box 1 protein (HMGB1). Treatment of Wobbler mice with CORT 113176 reversed the abnormalities of motoneurons and down-regulated proinflammatory mediators and glial reactivity. Expression of glutamate transporters GLT1 and GLAST mRNAs and GLT1 protein was significantly enhanced over untreated Wobblers. In summary, antagonism of GR with CORT 113176 prevented neuropathology and showed anti-inflammatory and anti-glutamatergic effects in the spinal cord of Wobbler mice.